Statement of Surveillance Priorities-Revisions of Economic Priorities and Progress on Operational Priorities. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2009)
This paper recommends changes to the economic priorities of the Statement of Surveillance Priorities (SSP) and provides an update on actions taken towards implementing the operational priorities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet
Keywords: Financial Sector Surveillance; Fund-FSB Early Warning Exercise; Fund's Work; Fund; PP